Spin-offs: Corporate Social Responsibility Perspective - Niittymäki, Miikka (My University, 2021)
This thesis investigates the impact of corporate social responsibility on the firm’s success in a corporate spin-off. The scope of this study is to explore whether spin-offs announced and completed in the 21st century are able to produce abnormal returns and whether firms with high corporate social responsibility are capable to gain even greater returns around the announcement date. In addition to short-term performance, this thesis also examines how the firms do in the long-term. An event study is used to investigate stock market reactions to spin-off announcements. In addition to announcement returns, the long-term returns are also computed for the parent companies to determine whether the performance is sustainable. Data used in the study consists of 164 U.S. market spin-offs that were announced and completed between the years 2002 and 2018. To provide new insights on how corporate social responsibility impacts the stock returns, the parent firms initiating the spin-offs are divided into high and low ESG portfolios to analyze how corporate social responsibility affects firms’ performance. The resulted cumulative average abnormal returns are regressed against different variables to identify sources of the value. Consistent with the previous research, this study finds evidence on spin-offs generating abnormal returns around the announcement date. Moreover, the firms with high corporate social responsibility seem to exhibit higher abnormal returns in the short term than low ESG firms. When breaking down the ESG factor to its sub-components and regressing these variables against resulted CAAR, the study finds the environmental and social components to express positive and significant association with announcement returns. Although the study finds high ESG firms to gain superior returns to low ESG firms in the long term, these results appear statistically insignificant. Overall, the results from this study contribute to the existing literature by suggesting that investors do benefit from the company’s high corporate social responsibility during the spin-offs and firms should actively manage their responsible image.
Keywords: corporate responsibility; social responsibility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance